The 'real' explanation of the PPP puzzle - Nicholas Ford; Charles Yuji Horioka (Osaka University, Institute of Social and Economic Research (ISER), 2016)
This article shows that global financial markets cannot, by themselves, achieve net transfers of financial capital and real interest rate equalisation across countries and that the integration of both global financial markets and global goods markets is needed to achieve net transfers of capital and real interest rate equalisation across countries. Thus, frictions (barriers to mobility) in one or both of these markets can impede the net transfer of capital between countries, produce the Feldstein and Horioka (1980) finding of high saving-investment correlations, and prevent real interest rates from being equalised across countries. Moreover, frictions in global goods markets can explain why real exchange rates deviate from PPP (purchasing power parity) for extended periods of time and can therefore also explain the PPP puzzle. Thus, we are able to resolve 2 of Obstfeld and Rogoff's (2000) "6 major puzzles in macroeconomics" with essentially the same explanation.
Keywords: E40; F21; F31; F32; F36; G15; 330; Exchange rate volatility; Feldstein-Horioka paradox or puzzle; financial market integration; goods market integration; international capital flows; international capital mobility; net transfers of capital; PPP puzzle; purchasing power parity puzzle; real interest rate equalisation; real interest rate parity; saving-investment correlations; Kapitalmobilität; Markteintritt; Handelshemmnisse; Kapitalverkehrskontrolle; Kaufkraftparität; Kapitalmobilität; Internationaler Finanzmarkt; Internationale Wirtschaft; Unvollkommener Markt